Logic, God and Metaphysics
IX, 153 p.
Keywords: The papers in this volume are in honor of Bowman L. Clarke. Bowman Clarke earned degrees from Millsaps College, the University of Mississippi, and Emory University in Atlanta, Georgia, including the PhD in philosophy from Emory in 1961. He spent most of his academic career, a total of twenty-nine years, as a member of the Philosophy Department of the University of Georgia, Athens, Georgia, from which he retired in 1990. He also served as Head of the Department for several years. He has held many positions of distinction in professional societies, including President of the Georgia Philosophical Society, President of the Society for the Philosophy of Religion, and President of the Southern Society for Philosophy and Psychology. He also served as Editor-in Chief of the International Journal for the Philosophy of Religion from 1975-1989. Professor Clarke is the author of Language and Natural Theology (The Hague: Mouton and Co. , 1966) as well as numerous articles in professional journals. He has made major contributions in the areas of the philosophy of religion, the study of the philosophy of Alfred North Whitehead, and the development of the calculus of individuals. ix J. F. Harris (ed. ), Logic, God and Metaphysics, ix. © 1992 Kluwer Academic Publishers. Introduction The title for this volume, Logic, God, and Metaphysics, was chosen very carefully and deliberately. The papers in this volume are directed at the issues and problems which lie in the domain of the juncture of these three different areas of philosophical inquiry.